Pregnancy Outcomes of Women Receiving Compounded 17 α-Hydroxyprogesterone Caproate for Prophylactic Prevention of Preterm Birth 2004 to 2011 - Sibai, Baha M.; Istwan, Niki B.; Palmer, Beverly; Stanziano, Gary J. (American Journal of Perinatology, 2012)
Objective To examine pregnancy outcomes of women receiving weekly compounded 17 α-hydroxyprogesterone caproate (17P) injections through a home nursing program compared with those reported in a multicenter trial by the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) Network.Methods The study sample was comprised of patients receiving compounded 17P through a home nurse administration care management program. Included were women with current singleton gestation and prior spontaneous preterm birth (SPTB) initiating 17P between 16 and 20 weeks. Maternal characteristics and pregnancy outcomes were compared between study group and NICHD Network trial patients.Results Women (n = 5493) received a mean of 16.9 ± 4.0 injections. Of the 92,700 injections, 98.4% were administered within the recommended 5- to 9-day interval. Recurrent SPTB occurred in 28.3%. The overall rate of SPTB at <37 weeks was similar for black and nonblack women (p = 0.592). Within black or nonblack groups, preterm birth rates at <37 weeks were similar regardless of gestational age at start of 17P (p = 0.894 and p = 0.374, respectively). These results were similar to those reported in the multicenter trial. Fetal and neonatal death occurred in 0.8% (46/5493). No significant difference was observed in rate of fetal or neonatal death by gestational age at initiation of 17P (p = 0.478).Conclusion Home nurse administration of compounded 17P is safe and effective.
Keywords: 17 alpha-hydroxyprogesterone caproate; compounded 17P; Makena; preterm birth prevention; safety